(untitled) (International Journal of Food and Nutritional Sciences, 2022)
One of the strongest regulators in India is the “Securities and Exchange Board of India (SEBI)”. As the overseer of the Indian securities market, it has a variety of enforcement tools at its disposal, including the ability to impose financial penalties, order the forfeiture of illegal gains made by violators, impose capital raising restrictions on businesses, and bar market participants from engaging in capital market activity. Although the law has expanded SEBI’s enforcement authority over time, it neither specifies which infractions would result in which enforcement consequence nor establishes proportionality requirements for various offences or offenders.The research on SEBI’s contribution to this growth and development is scant and somewhat out of date. By updating the changes in the securities markets throughout time, this paper updates the previous research. By improving the framework for assessing the appropriateness of institutional arrangements under SEBI and afterwards assessing whether the legislative arrangements at SEBI’s disposal are adequate assure a well-functioning securities market, it adds to the body of existing research. This study will serve as a crucial starting point for a more thorough assessment of SEBI’s contribution to the operation of the “Indian securities market”.